Evolution of the free volume and glass transition temperature with the degree of cure of polybutadiene rubbers - Mansilla, Marcela Angela (2013)
An investigation of the influence of the cure time on the glass transition temperature and nanostructure for two isomers of polybutadiene rubbers, CB25 (97% cis) and CB55 (38% cis), vulcanized at 433 K is presented. The samples were prepared with sulphur and TBBS (N-tbutyl- 2-benzothiazole sulfenamide), and several crosslink densities were achieved at the different selected cure times. The studies on the samples were carried out using differential scanning calorimetry and positron annihilation lifetime spectroscopy. The variation of the glass transition temperature with the degree of cure and its relation with the crosslink density is analyzed for each type of isomer. A correlation between the free nanohole volume and the crosslink density is also analyzed. From swelling tests, the absorbed solvent at room temperature is discussed in terms of the obtained free nanohole volumes, showing a correspondence between these parameters. In the frame of the obtained results, the cis to trans isomerisation of the elastomer with high cis content during the vulcanization is discussed.